2005
DOI: 10.1038/ng1533
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection and prognostic modeling of overt stroke in sickle cell anemia

Abstract: Sickle cell anemia (SCA) is a paradigmatic single gene disorder caused by homozygosity with respect to a unique mutation at the beta-globin locus. SCA is phenotypically complex, with different clinical courses ranging from early childhood mortality to a virtually unrecognized condition. Overt stroke is a severe complication affecting 6-8% of individuals with SCA. Modifier genes might interact to determine the susceptibility to stroke, but such genes have not yet been identified. Using Bayesian networks, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
251
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(260 citation statements)
references
References 31 publications
5
251
0
4
Order By: Relevance
“…We hypothesized that these and other candidate genes might modulate the pathobiology of sickle cell disease. In previous work, we found that SNPs in some genes of this pathway were associated with sickle cell stroke, osteonecrosis, and leg ulceration [13,14]. These results led us to follow-up studies of additional genes and SNPs in the TGF-b/BMP pathway.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We hypothesized that these and other candidate genes might modulate the pathobiology of sickle cell disease. In previous work, we found that SNPs in some genes of this pathway were associated with sickle cell stroke, osteonecrosis, and leg ulceration [13,14]. These results led us to follow-up studies of additional genes and SNPs in the TGF-b/BMP pathway.…”
Section: Discussionmentioning
confidence: 85%
“…We and others have attributed this heterogeneity to the effects of genes that modulate the pathobiology initiated by the sickle hemoglobin (HbS) mutation [reviewed in 12]. Previously, we reported associations among genes in the TGF-b/BMP pathway with other sickle cell disease subphenotypes, including stroke, osteonecrosis, and leg ulcers [13][14][15]. The TGF-b/BMP pathway has also been implicated in the development of diabetic nephropathy [reviewed in [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…KL, ANXA2, and BMP-6 were also shown to be associated with other vascular complications in SCD such as priapism [10] and stroke [12], suggesting a common underlying molecular basis for these vascular complications.…”
mentioning
confidence: 98%
“…The phenotype in patients with SCD is determined by the interaction of both genetic and environmental factors, of which some have been identified [1,[4][5][6]. It is important to increase our understanding of factors that contribute to a severe clinical course.…”
Section: Introductionmentioning
confidence: 99%